PHOTOCATALYTIC DEGRADATION OF METHYLENE BLUE USING IRON OXIDE NANOPARTICLES SYNTHESIZED USING ANNONA MURICATA LEAF EXTRACT - JOSE, BEENA; THOMAS, FEMY (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Objective: The objective of the present study is the synthesis of iron oxide nanoparticles using Annona muricata aqueous leaf extract, characterization of the synthesized nanoparticles and evaluation of the antibacterial, photocatalytic activity and cytotoxicity. Methods: The iron oxide nanoparticle was synthesized using Annona muricata aqueous leaf extract and the crystal structure of the iron oxide nanoparticle was determined by UV-Visible spectroscopy, Transmission Electron Microscopy (TEM), Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR). The in vitro cytotoxicity of iron oxide nanoparticles was evaluated using Dalton’s lymphoma ascites cells and the antibacterial assay was conducted using agar well diffusion method. Results: The UV-Visible spectrum of iron oxide nanoparticle showed a maximum absorption peak at 265 nm. This is the XRD pattern of iron oxide nanoparticles exhibited a distinct peak at 26.029 (2θ), accounting for crystal plane (211). SEM images revealed that the synthesized iron oxide nanoparticles were aggregated as irregular sphere shapes with rough surfaces. TEM image reveals the size of the synthesized iron oxide nanoparticles are spherical in shape with an average size of 20 nm. Green synthesized iron oxide nanoparticles using Annona muricata leaf extract effectively degraded methylene blue dye. Conclusion: This study showed that the synthesized iron oxide nanoparticles using Annona muricata aqueous leaf extract exhibited pronounced antibacterial, anticancer and photocatatytic activity and can be used in the textile industry for the purification of water contaminated with carcinogenic textile dyes. It can also be used as an external antiseptic in the prevention and treatment of bacterial infections.